Population trends and distribution of indigenous pigs in India - Rahul Behl,; PK Vij,; SK Niranjan,; Jyotsna Behl,; Arjava Sharma, (Journal of Livestock Biodiversity, 2025)
Indian indigenous pigs have unique features, including their adaptation for survival under most adverse conditions of nutrition, disease resistance, heat tolerance and ability to produce meat with comparatively less fat. The present status of indigenous pigs was evaluated in terms of their distribution and population trend. It is estimated that population of indigenous pigs will fall to 60.70 lakhs by 2025. Some regions in India still have sizable population of indigenous pigs. North-Eastern region of Assam comprising districts of Dhemaji, Lakhimpur and Sonitpur house about 4.28 percent of the indigenous pig population of India. Bhojpur district in Bihar has the highest population of indigenous pigs (128674) in the country. However, the decreasing population of indigenous pigs vis a vis increasing population of exotic and crossbred pigs indicate that the indigenous pigs require immediate care and attention to arrest the declining trend in their population.